Implementation of Preemptive and Preventive Policies at Buay Police Station Peliung East Oku Police Station - Albert, Jhoni; Sobri, Kgs M.; Widodo, Slamet; Putra, Raniasa (PERSPEKTIF, 2024)
This study aims to analyze and explain the implementation of preemptive and preventive policies of the National Police, especially in the context of non-investigation policies, at the Buay Pemuka Peliung Police Station, East OKU Police. The research method used was a qualitative description involving key informants such as Kasat Kanit reskrim, Kanit reskrim, and reskrim officers from the police station. Primary data are obtained through interviews, while secondary data are obtained from literature and related documents. The results showed that the implementation of preemptive and preventive policies of the National Police at the Polsek has had a significant impact on efforts to prevent and overcome potential crimes and security disturbances before they occur. Community support, clear understanding, and sufficient information are supporting factors while inhibiting factors include vagueness in policy content and limited resources. With a deeper understanding of the factors influencing policy implementation, it is hoped that the National Police can develop more effective strategies for maintaining public security and order.